Coordenador pedagógico e seus processos formativos: análise das pesquisas sobre a temática - Silva, Ana Carolina Leite da (2021)
The present research has as its general objective to investigate the theoretical-methodological foundations about how the formative constitution of the Pedagogical Coordinator is developed in its different processes and constitutive spaces, that is, in his graduation period, specialization and in the daily school life. The specific objectives of the dissertacion consist of (i) to carry out a historical review of legislation, viewing the changes in the nomenclature of the current Pedagogical Coordinator; (ii) to identify how the training processes of the Pedagogical Coordinator constitute their pedagogical practices; (iii) to map, through a Meta-Research, what the researches present in Capes' theses and dissertations say about the formation of the Pedagogical Coordinator. The study seeks to answer the following question: how the Pedagogical Coordinator in his different processes and spaces constitutive, whether in his graduation period, specialization or in everyday school life, seek to develop his formative constitution? It is a basic, bibliographical and documentary research. Structurally, in addition to the introduction, the dissertation is organized into fourth chapters. The second chapter addresses the contextualization of the historical formative path that led the Educational Supervisor to become Pedagogical Coordinator. The third, presents the educational processes of the Pedagogical Coordinator in his different training spaces. In the fourth chapter, through a Meta-research systematizes what the researches say about the Pedagogical Coordinator, using as analysis the following categories: a) How the selected researches comprehend the Pedagogical Coordinator, a task and supervisor agent of the actions carried out by the teachers or the one who develops a horizontal relationship, based on democratic management and that seeks to assist in the training of teachers? What emphasis is given to the work of the Pedagogical Coordinator? b) Are the selected researches of practical or theoretical nature? c) What are the theoretical references used in these researches? As a result of research, we have identified that the possible paths for the actions of the Pedagogical Coordinator are varied, what is behind their effective actions (management model) is what will make this professional acquire the recognition and training he deserves.